ACTION RESEARCH IN DIGITAL ACTIVISM COLLABORATION FOR EFFECTIVE CAMPAIGNS TO ADVOCATE FOR THE RATIFICATION OF THE SEXUAL VIOLENCE CRIME LAW - Yulita, Christina; Rachmawati, Tutik (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This paper discusses the learning of digital activism collaboration to create an effective campaign in encouraging the ratification of the Law on the Elimination of Sexual Violence (UU TPKS) using the Participation Action Research (PAR) model. The PAR model in digital activism collaboration for effective campaigns is carried out in two stages, namely the stage of creating knowledge and the stage of determining joint actions until the TPKS Law can be passed. Asset mapping and speech of survivors methods in generating emergency knowledge information so that the TPKS Law can be discussed and passed. In a collaborative process, digital activism produces campaign messages and various forms of content to encourage the ratification of the TPKS Law through posters, videos, online discussions and online petitions that are disseminated using digital platforms from various social media joined in a network of civil society organizations that move together for the ratification of the TPKS Law.